Structure, conduct, and performance analysis of the seaweed market in eastern Indonesia: a case study from Rote Ndao - Naninuna, Putra H.; Nendissa, Doppy Roy; Theresia Kiak, Novi; Pellokila, Marthen Robinson; Tshilowa, Phathutshedzo Fancy (Journal of Agricultural Socio-Economics (JASE), 2025)
Rote Island holds significant potential for seaweed development; however, the existing marketing system has yet to provide adequate welfare guarantees for seaweed farmers, as well as for other market participants. This study aims to analyze the structure, conduct, and performance of the seaweed market in Rote Barat District, Rote Ndao Regency, using the Structure-Conduct-Performance (SCP) approach. A mixed-methods research design was employed, with primary data collected through questionnaires and interviews involving 38 seaweed farmers and other market actors. The findings indicate that the market structure is oligopsonistic, with a concentration ratio (CR4) of 17.49% and a Herfindahl-Hirschman Index (HHI) of 10,000, reflecting a highly concentrated market. Barriers to market entry are also substantial, as evidenced by a Minimum Efficiency Scale (MES) of 62%. In terms of market conduct, prices are determined unilaterally by large traders and aggregators, while farmers tend to act as price takers. Market performance reveals high marketing margins and low farmer shares, indicating an unequal distribution of profits that disadvantages producers. Therefore, policy intervention and institutional strengthening, such as the formation of seaweed cooperatives, are necessary to foster a more transparent and equitable market system.